2019
DOI: 10.2174/1381612825666190619125426
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of Glucocorticoid-Induced Osteoporosis with Bisphosphonates Alone, Vitamin D Alone or a Combination Treatment in Eastern Asians: A Meta-Analysis

Abstract: Background: Glucocorticoid (GC)-induced osteoporosis and fractures have become a serious problem for Eastern Asians. Bisphosphonates (BPs), vitamin D and a combination treatment are effective methods to prevent and treat GC-induced osteoporosis. Objective: The study aimed to compare the efficacy of BPs, vitamin D and a combination treatment for preventing and managing GC-induced osteoporosis in Eastern Asians. Methods: A comprehensive search in the PubMed, EMBASE, Web of Science and Cochrane CENTRAL datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Increase in BMD by BP + ELD-treated osteoporotic patients is associated with the serum calcium level within the reference interval [ 16 ]. However, some studies indicated that compared with the BP-associated combination therapy, the BP treatment alone significantly increased the therapy effect in osteoporotic patients [ 17 19 ]. The clinical advantages of BP alone in the treatment of osteonecrosis compared with combined therapy have also been confirmed by multi-center studies [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increase in BMD by BP + ELD-treated osteoporotic patients is associated with the serum calcium level within the reference interval [ 16 ]. However, some studies indicated that compared with the BP-associated combination therapy, the BP treatment alone significantly increased the therapy effect in osteoporotic patients [ 17 19 ]. The clinical advantages of BP alone in the treatment of osteonecrosis compared with combined therapy have also been confirmed by multi-center studies [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…After double checking and reading the title and abstract of the results, we included 38 SRs for full-text reading. After excluding a narrative review, a network meta-analysis, and animal experiments, 6 SRs [17][18][19][20][21][22]…”
Section: Retrieval Results Of Literaturementioning
confidence: 99%
“…Primary outcome bMD of the lumbar spine (LSbMD) LSBMD was reported in six SRs [17][18][19][20][21][22]. Compared with low-dose BPs, standard-dose BPs improved the LSBMD (MD: 0.95 %, 95 % CI: 0.37 % to 1.53 %, p < 0.001).…”
Section: Effects Of Pharmacological Treatments For Giopmentioning
confidence: 99%
“…According to the evaluation results of the AMSTAR-2 tool, the 6 SRs included in this review included 2 high-quality [17,18], 2 low-quality [20,21], and 2 critically low-quality SRs [19,22]. The specific details of the methodological quality evaluation are shown in ▶Table 2.…”
Section: Methodological Quality Evaluationmentioning
confidence: 99%